2015
DOI: 10.1111/jpi.12279
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates Leishmania (L.) amazonensis infection by modulating arginine metabolism

Abstract: Acute inflammatory responses induced by bacteria or fungi block nocturnal melatonin synthesis by rodent pineal glands. Here, we show Leishmania infection does not impair daily melatonin rhythm in hamsters. Remarkably, the attenuated parasite burden and lesion progression in hamsters infected at nighttime was impaired by blockage of melatonin receptors with luzindole, whereas melatonin treatment during the light phase attenuated Leishmania infection. In vitro studies corroborated in vivo observations. Melatonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 54 publications
1
64
1
8
Order By: Relevance
“…( L .) amazonensis , probably by reducing the uptake of L-arginine and polyamine production, then supplementation with putrescine allow the infectivity44. Indeed, the deprivation of L-arginine decreases ornithine and putrescine levels but does not change the levels of spermidine, spermidine or agmatine in promastigotes45.…”
Section: Discussionmentioning
confidence: 99%
“…( L .) amazonensis , probably by reducing the uptake of L-arginine and polyamine production, then supplementation with putrescine allow the infectivity44. Indeed, the deprivation of L-arginine decreases ornithine and putrescine levels but does not change the levels of spermidine, spermidine or agmatine in promastigotes45.…”
Section: Discussionmentioning
confidence: 99%
“…Human colostrum monocytes, incubated with Escherichia coli enteropathogenic or zymosan, synthesize melatonin after a time lag of 20 min . RAW 264.7 macrophages also synthesize melatonin after incubation with LPS, zymosan, or the parasite Leishmania amazonensis . The common step for all this experimental models is that melatonin synthesis is driven by NF‐ κ B nuclear translocation and is dependent on Aa‐nat transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the effect of darkness on endothelial cells primes the expression of microRNAs that negatively regulate cell adhesiveness, inflammatory response, and proliferation [44]. Melatonin synthesized by phagocytes acts in a paracrine manner favouring the phagocytosis of bacteria, fungi, parasites, and cellular debris [17, 41, 45, 46]. The synthesis of melatonin by the pineal gland is restored before the end of the acute inflammatory response, due to the inhibition of NF- κ B by glucocorticoids released from the adrenal gland [29, 47, 48].…”
Section: Melatoninergic Systemmentioning
confidence: 99%